An analysis of narrative discourse in harry potter by j.k rowling - Lê,Thanh Thúy An; Trần Quang Hải (ĐHĐN : ĐHĐN., 2015)
The study attempts to investigate linguistic features of narrative discourse on conversational openings and questions in conversations. This research also aims to contribute to the other linguistic research such as on language development, to help English learners in opening a conversation or make question in conversation. 924 conversational openings and 2258 questions are collected from the novel “Harry Potter” by J.K Rowling. The study is carried out through the adoption of descriptive, quantitative, and qualitative. The research found that a full description and analysis of the strategies of opening a conversation in the first four Harry Potter books. The opening of conversation is studied in different functions. The opening phase is firstly marked by greetings, identification. The summon-answer sequence is also found to get attention of the hearer, and then considered a pre-opener. The utterances are found in opening conversations with requesting and inquiring, expressive and informative functions. The requesting and inquiring openings include asking on situations, requesting for action, asking for information, direction and opinion, asking for permission, offering, and inviting. The expressing acts for opening are complaining, apologizing, exclaims or statements expressing various feelings, complimenting and remarking. The final type is informative opening which distinguishes between informing and reporting. In order to help language learners to open a conversation, the implication for teaching of this problem was mentioned. Besides, the research found six types of questions in terms of semantic and syntactic features. These are alternative questions, declarative questions, hypothetical questions, indirect questions, wh-questions, and yes-no questions. Through the analysis, the type of questions could be clearly and more understanding. It helps language learners to make questions easily
Master thesis in social sciences and humanities.
Keywords: analysis of narrative discourse in harry potter by j.k rowling; narrative discourse -- harry potter